Attend to R&D woes at varsities - Abd Razak, Dzulkifli (2005)
University reseachers were delighted when Deputy Prime Minister Datuk Najib Razak recently said procedures putting a strain and constraints on R&D at the universities should be reviewed. LIKE a breath of fresh air, Malaysian scientists were treated to a very refreshing viewpoint (bordering on a directive) by Deputy Prime Minister Datuk Seri Najib Razak recently. The event took place during a ceremony to recognise the achievements of our scientists, including for exceptional performance at the international level. No less than 100 researchers and scientists were singled out, based on their achievements in the various scientific meetings in Geneva, Pittsburgh, Nuremberg, London and Seoul. What was more meaningful was that these were innovation and invention expositions where researchers and inventors the world over participated to display their creative inventions for competition.